RP-LC method for simultaneous determination of sulfamethoxazole and trimethoprim content in veterinary drugs - Tahan, Gabriela Padovani; Machado, Simone Caetani; Malaguti, Evandro Conti; Maia, Patrícia Penido; Rath, Susanne; Martins, Isarita (Eclética Química, 2016)
This study describes the development of a method for simultaneous analysis of sulfamethoxazole (SMX) and trimethoprim (TMP) through the use of high-performance liquid chromatography/ultraviolet detector, with the application to veterinary medicines. Satisfactory chromatographic separation of SMX and TMP was isocratically with a C18 column (150 x 4.6 mm, 5 mm). A mobile phase consisting of water, pH 3.5, and methanol (60:40, v/v) was delivered at a flow rate of 1.0 mL min-1 for five minutes and then, increased to 1.8 mL min-1. Detection of the drugs was performed at 213 and 230 nm. Linearity was demonstrated in the range of 5 to 70 mg mL-1 for SMX and 1 to 30 mg mL-1 for TMP (r2 ≥ 0.99 for both compounds). The relative standard deviation was ≤ 5%, and the comparison of the results with the concentrations reported on the drug labels indicated that the quantification was accurate. The resultant stressed samples were analysed by the method. The proposed method shows great potential for simultaneous analysis of the drugs evaluated and represents a new alternative approach to quality control of veterinary medicines.